Computation or Revolution. (May 2014) - Morel, Philippe; Gramazio, Fabio; Kohler, Matthias
Abstract The connection between technology and society today remains as compelling as in Le Corbusier's time, with views from social commentators, scientists and economists habitually polarising around the adverse or positive impact of technological change. Tracing the roots of computation and robotics back to the Second World War, Philippe Morel of EZCT Architecture & Design Research redefines the position of artificial intelligence, robots and computation in architecture, highlighting the potential of computers to perform precise calculations – and outperform human intelligence in almost every way.